Impact of appetitive and aversive outcomes on brain responses: linking the animal and human literatures - Bissonette, Gregory B.; Gentry, Ronny N.; Padmala, Srikanth; Pessoa, Luiz; Roesch, Matthew R. (Frontiers in Systems Neuroscience, 2014)
Decision-making is motivated by the possibility of obtaining reward and/or avoiding punishment. Though many have investigated behavior associated with appetitive or aversive outcomes, few have examined behaviors that rely on both. Fewer still have addressed questions related to how anticipated appetitive and aversive outcomes interact to alter neural signals related to expected value, motivation, and salience. Here we review recent rodent, monkey, and human research that address these issues. Further development of this area will be fundamental to understanding the etiology behind human psychiatric diseases and cultivating more effective treatments.